MrERF, MrbZIP, and MrSURNod of Medicago ruthenica Are Involved in Plant Growth and Abiotic Stress Response - Wu, Rina; Xu, Bo; Shi, Fengling (Frontiers in Plant Science, 2022)
Abiotic stresses affect plant growth and productivity. The outstanding stress resistance of Medicago ruthenica makes it a desirable gene resource to improve the stress tolerance of other plants. The roles of three differently expressed genes [(DEGs) (MrERF, MrbZIP, and MrSURNod)] from M. ruthenica in stress resistance have not been fully elucidated. Therefore, we constructed their expression vectors, transformed them into tobacco, and subjected transgenic lines to abiotic stresses. Through comprehensive bioinformatics, transcriptomic, morphological, and physiological analyses of transgenic lines, we have revealed the critical role of these three DEGs in plant growth and abiotic stress response. The upregulation of genes enhanced the germination rate, biomass, root length number, etc. Additionally, the accumulation of osmolytes increased the activity of antioxidant enzymes. These genes are also associated with improved seed yield, increased branching, and early flowering, thereby shortening the growth period. Potentially, this is one of the ways for tobacco to cope with stress. Furthermore, the resistance of transgenic tobacco expressing MrERF or MrbZIP was better than that with MrSURNod. MrERF and MrbZIP can improve drought and salt tolerance of plants, whereas MrSURNod is beneficial in improving drought and cold resistance. Moreover, MrERF or MrbZIP can promote root elongation and increase the root number, whereas MrSURNod mainly promotes root elongation. This may be the reason why stress resistance conferred by MrSURNod is weaker than that associated with the other two genes. Overall, MrERF, MrbZIP, and MrSURNod positively modulate plant growth and stress tolerance.